2012
DOI: 10.5210/fm.v17i10.3984
|View full text |Cite
|
Sign up to set email alerts
|

Social media discussion forums and product innovation - The way forward?

Abstract: The purpose of this paper is to examine the potential use of social media discussion forums in product innovation. The literature shows the value of sport addicts and hobbyists as innovators in product innovation; hence this study is related to sports. This is an empirical study based on substantial data collected from 28 discussion forums. Altogether 2,178 discussions related to heart rate monitors have been evaluated for this paper. Discussion forums can be regarded as a source of product innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Discussion forums are sources of incremental product innovation (Haavisto, 2012) and can be used to build communities of innovation (Jeppesen & Molin, 2003) and create electronic word-of-mouth (e-WOM) in product development (Andreassen & Streukens, 2009). This research found companies that used discussion forums focusing internal staff, seeking to centralize and facilitate communication with collaborators.…”
Section: Qualitative Approach -Companiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion forums are sources of incremental product innovation (Haavisto, 2012) and can be used to build communities of innovation (Jeppesen & Molin, 2003) and create electronic word-of-mouth (e-WOM) in product development (Andreassen & Streukens, 2009). This research found companies that used discussion forums focusing internal staff, seeking to centralize and facilitate communication with collaborators.…”
Section: Qualitative Approach -Companiesmentioning
confidence: 99%
“…In addition, search engines are used to identify relevant content to business (Brin & Page, 1998;Singhal & Nagar, 2013). Companies also have used discussion forums, virtual meeting places for interaction between people who share same interests (Nambisan & Baron, 2009;Haavisto, 2012). Social media facilitate user interactions and have been used and investigated for innovation.…”
Section: Introductionmentioning
confidence: 99%
“…It is also useful for constructing mutual trust with consumers and raising economic value for consumers (Noone, McGuire, & Rohlfs, 2011;Kate & Pavan, 2012). Information that consumers exchange through social media contains useful content for product improvement, new marketing strategies, and the promotion of sales (Haavisto, 2012;Idota, Bunno, & Tsuji, 2017). In other words, social media brings opportunities related to Customer Relationship Management (CRM) (Malthouse, Haenlein, Skiera, Wege, & Zhang, 2013).…”
Section: B Social Media Use In the Firmmentioning
confidence: 99%
“…Moreover, social media can be used for obtaining useful consumer needs for product innovation and enable collaboration with entities outside the firm. As mentioned above, a large number of studies examining the roles of social media in business focus mainly on marketing and the sales force; they analyze how social media are utilized for advertising their products, sampling consumer needs, surveying the reputation of products, and so on (Noone, et al, 2011;Agnihotri, Kothandaraman, Kashyap, & Singh, 2012;Groza, Peterson, Sullivan, & Krishnan, 2012;Haavisto, 2012;Hausmann, 2012;Kate & Pavan, 2012;Rodriguez, et al, 2012;Schultz, Schwepker, & Good, 2012;Luo & Zhang, 2013;Malthouse, et al, 2013). Useful content for product improvement and new marketing strategies are contained in information that users exchange through social media (Haavisto, 2012).…”
Section: Social Media and Product Innovationmentioning
confidence: 99%
“…Social media is also useful for constructing mutual trust with consumers and raising economic value for consumers [6,7]. Information that consumers exchange through social media contains useful contents for product improvement and new marketing strategies [8]. In other words, social media brings opportunities for customer relationship management (CRM) [9].…”
Section: Previous Literaturesmentioning
confidence: 99%